O PROCESSO DE NUCLEARIZAÇÃO DAS ESCOLAS RURAIS ISOLADAS E MULTISSERIADAS: UMA ANÁLISE A PARTIR DO MUNICÍPIO DE CANDÓI-PR, NO PERÍODO DE 1993 A 2000 - Abreu, Mariclaudia Aparecida de (2015)
This dissertation presents a discussion about the nuclearization process of rural schools isolated from the city of Candói in the state of Paraná, between the years 1993 to 2000. The research, qualitative approach, includes bibliographical study, documentary and interviews. Until the 1970s, according to the IBGE (2010), Paraná population was located in the field. During this period, there was also a large number of isolated rural schools, who met students of a given community in multigrade system. The documents show that schools were marked by structural problems, in which some professionals worked, most often, without qualifications and who also exercised function like cooker and janitor among other duties which may require a teaching and administrative work. From the 1970s, the situation is reversed, to the point in 1990 only 26.6% of the population remain in the countryside, according to IBGE data (2010). As a result, there is a drop in the number of enrollments in rural areas. It is at the height of this process we will discuss in this task the nuclearization of isolated rural schools with emphasis in the county of Candói. In this sense, the objective of this research was to analyze the reasons and the social and educational impact of this measure. For many, the text was divided into four chapters. In the first chapter we discuss the historical trajectory of rural education in Brazil and Parana. In the second chapter, we deepened a little more in the analysis of isolated and multisseriate rural school. The third chapter analyzes the nuclearization policy of isolated rural schools, seen as a solution to the problem of rural Paraná education. In the fourth chapter, we seek to rebuild, mainly through oral history, the materialization of the rural school in Candói between the 1980s and 1990, as well as analyze the nuclearization of the implementation process of the isolated rural schools in this county. Found by studying the current discourse at the time emphasized an improvement in the quality of education, as the nuclearization provide a school with a better physical infrastructure with qualified and pedagogical support. We also note that in practice, this measure coveted streamline costs, due to the concentration of several students in one building they share space, resources and equipment. Beyond this speech, we realize the existence of conflicts in the nuclearization deployment process, because of the significant changes that the measure imposed on sociocultural relations that existed in the various communities in which it occurred.